Effects of mothers' deaths on children's schooling in Matlab subdistrict, Bangladesh. Issue 2 (4th May 2017) - Razzaque, Abdur; DaVanzo, Julie; Ahmed, Shahabuddin; Hossain, Akhtar; Enamul Hoque, Mohammad; Alam, Nurul; Bhuiya, Abbas; Streatfield, Peter Kim
ABSTRACT: This quantitative analysis examines evidence for the impacts of mothers' death on the schooling of their left-behind children (ages 6–17 years) in the Matlab Health and Demographic Surveillance System (HDSS) area of the International Centre for Diarrhoeal Disease Research, Bangladesh. The analysis compared the completed levels of primary and junior secondary schooling in 2005 (respectively Class 1 among ages 6–17, Class 5 among ages 12–17 and Class 7 among ages 15–17) of children whose mothers had died during 1982–2005 (from maternal and/or nonmaternal causes, and any cause) with the completed schooling of children of surviving mothers in 2005. The results, after controlling for selected socioeconomic variables, indicate that children whose mothers had died had lower completion of schooling levels, and that those children from poorer households fared worst.